MARJIN PEMASARAN DAN BIAYA POKOK PRODUKSI (BPP) JAGUNG DI PROVINSI LAMPUNG - Darwis, Valeriana (Indonesian Journal of Socio Economics)
This study aims at identifying the value of prime production cost of one kilogram of corn and its marketing margin at trader level in Lampung Province. The study was conducted in November 2007 employing structured questionnaire towards 25 farmers and four corn traders. Data were analyzed using descriptive and marketing margin methods. The study shows that the main production cost was Rp 975 per kilogram and farmers gained benefit about 85 percent of invested farm inputs in one season. Farmers directly sold corns to collector and the collector sold them to big scale traders with the price ranging from Rp 1,800 to Rp 1,850 per kilogram. Big scale trader directly sold dried and packed corns to the store or animal feed industry about Rp 2,190 per kilogram.